Analysis of potential household transmission events of tuberculosis in the city of Belem, Brazil. (December 2018) - Conceição, Emilyn Costa; Guimarães, Arthur Emil dos Santos; Lopes, Maria Luíza; Furlaneto, Ismari Perini; Rodrigues, Yan Corrêa; da Conceição, Marília Lima; Barros, Wandyra Araújo; Cardoso, Ninarosa Calzavara; Sharma, Abhinav; Lima, Luana Nepomuceno Gondim Costa; Gomes, Harrison Magdinier; Duarte, Rafael Silva; et al.
Abstract: Tuberculosis (TB) is an infectious disease with a higher risk for infection and disease among household contacts (HHC). Here, we report a molecular epidemiology-based approach to study disease transmission and the genetic characteristics of Mycobacterium tuberculosis (Mtb) strains among HHC in the city of Belem, the capital of the state of Para in north Brazil. The study included 63 TB patients belonging to 26 HHC groups (HHC1 to HHC26). Spoligotyping and 24-loci Mycobacterial Interspersed Repetitive Unit - Variable Number of Tandem Repeat (MIRU-VNTR) revealed indistinguishable bacterial genotypes among 26 patients in 14 (53.8%) HHC groups. Drug susceptibility testing (DST) revealed that 45 (71.4%) of the Mtb isolates were multidrug resistant. The major cluster composed of isolates from five HHCs and on three of these, whole genome sequencing (WGS) was performed confirming their high genetic similarity. These results pinpoint the need for improved vigilance for TB control in households in the city of Belém. When comparing WGS versus phenotypic resistance detection methods as DST and Minimum Inhibitory Concentration (MIC) our data suggest that depending on the colonies selection, results may present variation.